Analysis Of Work Delay In Slum Quality Improvement Project Puday-Lapulu - Ardika, Made; Sufrianto, Sufrianto; Hujiyanto, Hujiyanto; Hawa, Sitti (Universitas Sulawesi Tenggara, 2023)
A construction project is an activity that aims to build facilities and infrastructure within the planned timeframe. The project can be defined as an organized effort or activity that uses the available budget and resources that must be achieved to achieve important goals, objectives, and expectations using the existing budget and resources, which must be completed within the planned timeframe so that the project does not experience delays. The purpose of this study was to determine how much work delays, the factors that cause work delays and how much influence the delay factors have on work delays in the Puday- Lapulu Slums Quality Improvement Project. The results of this study indicate the value of SV is Rp. (- 8.25 %) While the value of SPI < 1 is 0.896 < 1, based on the criteria for the value of SV and SPI, it can be said that the work is late and has poor performance. Factors that influence delays are aspects of labor and materials. While the large influence of delay factors on work delays that is 10,9 %.